2011
DOI: 10.1007/s00464-011-1667-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tissue compression on circular stapler line failure

Abstract: Maximum intraluminal pressure of an anastomosis in this porcine model correlated most strongly with the compression of the tissue involved in the anastomosis. This experimental model provides a framework for constructing a systematic approach to creating an anastomosis with sufficient mechanical strength. However, this study was not intended to establish the upper range of tissue compression beyond which a permanent tissue injury may occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…As early as the 1960s, Astafiev’s experiments with stapling devices of his era demonstrated that “The defined values of isolated organ walls cannot serve as initial data for estimation of suturing gap range in instruments, for they do not include the tissue turgor that depends on blood filling, tissue fluid pressure, and other factors.”23 Consequently, each tissue type must be appropriately compressed before suturing or stapling to achieve the optimal amount of perfusion and homeostasis for healing. More recent studies lend further support to the concept that increased compression is associated with desirable outcomes: lower leak rates,24 increased intraluminal pressure,25 improved hemostasis,24 and minimized wound contraction, potentially leading to decreased stricture rates 24,26,27…”
Section: A Framework For the Study Of Device Tissue And Their Intermentioning
confidence: 85%
“…As early as the 1960s, Astafiev’s experiments with stapling devices of his era demonstrated that “The defined values of isolated organ walls cannot serve as initial data for estimation of suturing gap range in instruments, for they do not include the tissue turgor that depends on blood filling, tissue fluid pressure, and other factors.”23 Consequently, each tissue type must be appropriately compressed before suturing or stapling to achieve the optimal amount of perfusion and homeostasis for healing. More recent studies lend further support to the concept that increased compression is associated with desirable outcomes: lower leak rates,24 increased intraluminal pressure,25 improved hemostasis,24 and minimized wound contraction, potentially leading to decreased stricture rates 24,26,27…”
Section: A Framework For the Study Of Device Tissue And Their Intermentioning
confidence: 85%
“…They demonstrated that the more the tissue was compressed, the stronger the anastomosis was (Myers et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Performing anastomosis on porcine stomachs and small intestines, Myers et al (2011) showed the importance of correct tissue compression generated by the staples. They demonstrated that the more the tissue was compressed, the stronger the anastomosis was (Myers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, we feel that the results after anastomosis by L-SST would most likely mimic the results of conventional SST. Leak tests are the most objective test for assessing anastomosis techniques and are widely used to determine the robustness of the anastomoses [19][20][21].…”
Section: Discussionmentioning
confidence: 99%